CICLO RUTA TURÍSTICA EN LAS PARROQUIAS CASACAY Y PROGRESO, CANTÓN PASAJE DE LAS NIEVES, PROVINCIA DE EL ORO - Zambrano Choez, Dayana Janeth (2018)
Ecuador is a country with an extensive and unparalleled natural and cultural wealth. The diversity of its four regions has given rise to hundreds of thousands of species of flora and fauna considered one of the 17 countries where the greatest biodiversity on the planet is concentrated. In the province of El Oro, Canton Passage are the parishes Casacay and Progreso, the Ministry of Tourism of Ecuador considers Casacay as one of the main tourist attractions of the country, due to its main river "Casacay", listed as one of the best natural water spas; while the Progreso parish has been characterized as a cocoa and banana producing area. The development of the cycle routes seeks to generate a recreational, sporting and non-competitive activity that combines physical activity and tourism consists of traveling by bicycle visiting the places that one finds in its path, this activity is done for pleasure. The Parroquias Casacay and Progreso del Cantón Pasaje contain a vast natural and cultural wealth, and it is important to develop the research work, which has as a General Objective: To elaborate a tourist route cycle in the parishes of Casacay and Progreso, Pasaje de las Nieves, province of El Oro. Following were three specific objectives that are detailed below: first specific objective; Carry out the tourist diagnosis of the parishes Casacay and Progreso, Pasaje de las Nieves, province of El Oro. The analytical method, the techniques of direct observation, interview, Tourist Diagnostic Matrix of Carla Ricaurte Quijano, Tourist Inventory Files of the Ministry of Ecuador and also support materials such as the Development Plan and Territorial Organization of each parish respectively and finally the matrix of strengths, opportunities, weaknesses and threats (SWOT) was used to determine the current situation of the parishes. The Second Objective; Propose the design of the tourist route cycle in the parishes of Casacay and Progreso, Pasaje de las Nieves canton, El Oro province. Tools such as the global positioning system (GPS) were used to make the coordinates, travel and distances of the attractions; photographic camera; the elaboration of a file to propose the signage of the cycle tourist route according to the Corporate Manual of Tourist Signaling of the MINTUR; In addition, the brand and name of the cycle route called "Cicloruta Balnearios Casacay - Progreso" and its slogan "Live the tourism on wheels" was also created, a script and itinerary of the route was also elaborated. The Third Objective; Socialize the results obtained during the realization of the project with the actors involved in it. Through the MARPP technique, the results obtained through the research carried out in the aforementioned parishes could be made known directly to the people involved, thus taking their opinions about the present research work. Regarding the conclusions of the thesis work, the proposal of the Touristic Cycle that integrates the parishes Casacay and Progreso is determined that will help to promote and disseminate the tourist attractions and to take 5 possession at a local and national level contributing in this way to the strengthening of tourism in the parishes. Finally, it is recommended to the community and the Decentralized Autonomous Government of the Parishes, Casacay and Progreso, to value the tourist attractions owned by the parishes, in order to take care of them, thus avoiding their deterioration and abandonment of the attractions to maintain the customs and traditions of the parishes